2010
DOI: 10.1111/j.1574-6968.2009.01890.x
|View full text |Cite
|
Sign up to set email alerts
|

Molecular strategy for identification inAspergillus sectionFlavi

Abstract: Aspergillus flavus is one of the most common contaminants that produces aflatoxins in foodstuffs. It is also a human allergen and a pathogen of animals and plants. Aspergillus flavus is included in the Aspergillus section Flavi that comprises 11 closely related species producing different profiles of secondary metabolites. A six-step strategy has been developed that allows identification of nine of the 11 species. First, three real-time PCR reactions allowed us to discriminate four groups within the section: (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
33
0
4

Year Published

2011
2011
2018
2018

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 61 publications
(39 citation statements)
references
References 37 publications
2
33
0
4
Order By: Relevance
“…We did not specify any species from these sections because the applied methods were sufficient only for sectional classifications. Due to morphological similarities among species from each section, specific DNA sequence data is required (16,(34)(35)(36)(37)(38).…”
Section: Resultsmentioning
confidence: 99%
“…We did not specify any species from these sections because the applied methods were sufficient only for sectional classifications. Due to morphological similarities among species from each section, specific DNA sequence data is required (16,(34)(35)(36)(37)(38).…”
Section: Resultsmentioning
confidence: 99%
“…1 Aspergillus oryzae and A. sojae are classified in the Aspergillus section Flavi , which also includes plant pathogen A. flavus and A. parasiticus that produces aflatoxins known to be carcinogenic substances. The analysis based on restriction-site polymorphisms of genes coding for 11 proteins and sequences of five of those genes suggested that A. oryzae is a species derived from A. flavus through human handling.…”
Section: Introductionmentioning
confidence: 99%
“…It should be pointed out that the identification of new species and restriction of the taxon in new groups are the result of a polyphasic taxonomic approach (Samson, Hong, & Frisvad, 2006;Klich, 2007;Godet & Munaut, 2010).…”
Section: Aflatoxins In Brazil Nutsmentioning
confidence: 99%